Social Media and Cybercrimes - et. al., Lama Almadhoor, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Users can communicate with each other by posting multimedia materials such as audio, text, photographs, video, animation, and graphics via a forum known as social media networking through a website or application medium. Despite its benefits, Social media has posed a huge risk in various fields such as strategic interests and national security that leads to adverse impacts. Cybercriminals have turned to social media as an outlet for carrying out their criminal actions. Computers and the internet are used in carrying out cybercrimes by stealing other people’s identities as well as tracking down personal information and victims. There are several types of cyber-crimes. It is necessary to incorporate security measures and methods to control cyber-crimes. In this paper, we provide an overview of cybercrimes on social media. We will discuss common cybercrimes, their mitigation techniques, and protection in social media.